Diagnosability of expanded k-ary n-cubes with missing edges under the comparison model. Issue 1 (2nd January 2020) - Zhou, Zhipeng; Wang, Shiying; Ma, Xiaolei; Ren, Yunxia
ABSTRACT: The diagnosability of multiprocessor systems is an important research topic. In 2017, Wang et al. extended the k -ary n -cube and defined an expanded k -ary n -cube, which is a system topology structure with good properties. In this paper, we prove that the expanded k -ary n -cube has the strong local diagnosability property for n ≥ 2 and k ≥ 6, and it keeps this strong property even if there exist ( 4 n − 5 ) missing edges in it under the comparison model. GRAPHICAL ABSTRACT: